PEDAGOGICAL CONDITIONS FOR THE FORMATION OF BUSINESS SPEECH AMONG STUDENTS OF ECONOMIC FIELDS AT HIGHER EDUCATION INSTITUTIONS - Gulyamova, Dilfuza Ibodullaevna (THE INNOVATION ECONOMY, 2026)
The article examines the pedagogical conditions for developing business speech among students of economic fields at a university. The results show that the professional orientation of teaching, practice-oriented tasks, and the modeling of business communication situations improve the level of students’ communicative training.